Efficacy of free fibula flap for reconstruction of post traumatic long bone defect: retrospective study of eighteen cases - Sharma, Shobhit; Bera, Sudipta (International Journal of Research in Orthopaedics, 2019)
Background: Complex and segmental bone defects are common after resection of tumors and trauma involving long bones of the extremities. Free fibula flap is commonly practiced for complex oromandibular defects and bone reconstruction after sarcoma and bone tumor excision. But post traumatic bone reconstruction of extremities with free fubula is less commonly practiced and only reserved for long segmental reconstruction or as an alternative to distraction osteogenesis. We are presenting a retrospective analysis of surgical details and outcome of 18 cases with post traumatic long bone defect reconstructed with free fibula osteocutaneous flap. Methods: 18 patients with post traumatic composite or segmental long bone defect which were reconstructed with free fibula osteocutaneous flap (FFOCF) between 2014 to 2018 are included in this study. Operative details, success rate, bone healing, functional outcome and complications are reviewed retrospectively. Results: Success rate of flap surgery was 17/18 (94.44%). Bone gap was 6-17 cm and Skin paddle ranged from 10 cm × 8 cm to 15 cm × 10 cm. Bone healing, weight bearing outside cast and return to daily activity period were 8-16 weeks, 10-15 months and 12-18 months respectively. Non-union, malunion and stress fracture were noted in one,one and three patients respectively. Conclusions: Free fibula flap is a reliable method for reconstruction of post traumatic complex and segmental long bone defects. Quality of bone healing is good enabling resuming to early weight bearing and daily activities and high success rate. Free fibula flap may be procedure of choice for reconstruction of such bony injuries with the microvascular surgical facilities.